2022
DOI: 10.1093/cercor/bhac387
|View full text |Cite
|
Sign up to set email alerts
|

Age-related reorganization of functional network architecture in semantic cognition

Abstract: Cognitive aging is associated with widespread neural reorganization processes in the human brain. However, the behavioral impact of such reorganization is not well understood. The current neuroimaging study investigated age differences in the functional network architecture during semantic word retrieval in young and older adults. Combining task-based functional connectivity, graph theory and cognitive measures of fluid and crystallized intelligence, our findings show age-accompanied large-scale network reorga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 93 publications
4
15
0
Order By: Relevance
“…It is plausible that with age, with or without a diagnosis of MCI, there is less neural differentiation across retrieval and non‐retrieval trials compared with YA, and comparable neural resources (theta ERS and alpha ERD) are being used to facilitate retrieving and inhibiting object concepts during semantic memory processing (Cavanagh & Frank, 2014; Klimesch, 2012). This finding is consistent with the literature that suggests dedifferentiation and reduced segregation in neural activity in healthy aging (Koen & Rugg, 2019; Martin et al, 2023). However, these reduced neural differentiations in HA at later time frames do not seem to be sufficient to impact task performance.…”
Section: Discussionsupporting
confidence: 93%
“…It is plausible that with age, with or without a diagnosis of MCI, there is less neural differentiation across retrieval and non‐retrieval trials compared with YA, and comparable neural resources (theta ERS and alpha ERD) are being used to facilitate retrieving and inhibiting object concepts during semantic memory processing (Cavanagh & Frank, 2014; Klimesch, 2012). This finding is consistent with the literature that suggests dedifferentiation and reduced segregation in neural activity in healthy aging (Koen & Rugg, 2019; Martin et al, 2023). However, these reduced neural differentiations in HA at later time frames do not seem to be sufficient to impact task performance.…”
Section: Discussionsupporting
confidence: 93%
“…Existing studies have mainly focused on age-related changes in functional connections between pairwise nodes or sub-networks. [36][37][38] Our study concentrated on characterizing the lifespan trajectory of mean nodal similarity between each node and the remaining nodes in brain morphological networks. The regions with age-related significant linear declines in nodal similarity were mainly located in the temporal lobe, implying that the covariation of multiple morphological feature in these regions decreases with age.…”
Section: Discussionmentioning
confidence: 99%
“…MRI studies have shown that brain anatomical feature and structural covariance networks exhibited age‐related heterogeneous alterations during the process of development and aging, 1,11,34,35 but few studies have investigated the age‐related lifespan trajectories of the nodal similarity of each node in the morphological networks. Existing studies have mainly focused on age‐related changes in functional connections between pairwise nodes or sub‐networks 36–38 . Our study concentrated on characterizing the lifespan trajectory of mean nodal similarity between each node and the remaining nodes in brain morphological networks.…”
Section: Discussionmentioning
confidence: 99%
“…In the aging brain, semantic cognition is characterized by a shift of the functional network architecture, which is reflected by increased activity of the MDN (for a review, see Hoffman and Morcom, 2018) and greater functional connectivity between domain-general networks such as the default mode network (DMN) and dorsal and ventral attention networks during semantic processing (Martin et al, 2022). This shift has also been described as reduced specialization of “core” processing areas of a task and increased neural dedifferentiation (Grady, 2012; Park et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The pre-SMA was selected as target area since it has been associated with the semantic control network and the domain-general MDN (Fedorenko et al, 2013; Jackson, 2021) emphasizing its role in mediating cognitive control across domains. Moreover, the pre-SMA contributes more to semantic processing in older relative to young adults (Martin et al, 2022) and represents a hub region in task-related functional networks of older adults, facilitating integrative processing (Martin et al, 2022). Using a semantic judgment task with varying cognitive demands and a tone judgment task as non-verbal control task, we hypothesized that iTBS might show stronger effects on the more demanding semantic condition.…”
Section: Introductionmentioning
confidence: 99%